Small molecule, non-peptide p75 ligands inhibit Abeta-induced neurodegeneration and synaptic impairment. - Tao Yang; Juliet K Knowles; Qun Lu; Hong Zhang; Ottavio Arancio; Laura A Moore; Timothy Chang; Qian Wang; Katrin Andreasson; Jayakumar Rajadas; Gerald G Fuller; Youmei Xie; et al. (PLoS ONE)
The p75 neurotrophin receptor (p75(NTR)) is expressed by neurons particularly vulnerable in Alzheimer's disease (AD). We tested the hypothesis that non-peptide, small molecule p75(NTR) ligands found to promote survival signaling might prevent Abeta-induced degeneration and synaptic dysfunction. These ligands inhibited Abeta-induced neuritic dystrophy, death of cultured neurons and Abeta-induced death of pyramidal neurons in hippocampal slice cultures. Moreover, ligands inhibited Abeta-induced activation of molecules involved in AD pathology including calpain/cdk5, GSK3beta and c-Jun, and tau phosphorylation, and prevented Abeta-induced inactivation of AKT and CREB. Finally, a p75(NTR) ligand blocked Abeta-induced hippocampal LTP impairment. These studies support an extensive intersection between p75(NTR) signaling and Abeta pathogenic mechanisms, and introduce a class of specific small molecule ligands with the unique ability to block multiple fundamental AD-related signaling pathways, reverse synaptic impairment and inhibit Abeta-induced neuronal dystrophy and death.